Diversity and significance of eriophyoid mites (Acari: Eriophyoidea) associated with coniferous trees in Poland: a review - Kiedrowicz, Agnieszka; Lewandowski, Mariusz; Skoracka, Anna (Biological Letters, 2017)
Among the approximately 200 eriophyoid mite species associated with coniferous trees worldwide, 33 species (of the families Eriophyidae and Phytoptidae) infest conifers in Poland, and 24 of them can cause visible feeding symptoms. In this paper we discuss the importance of eriophyoid mites to coniferous plants in Poland and their potential impact on the decorative value of ornamental plants. We emphasize the general lack of knowledge about the diversity of eriophyoid mites associated with coniferous trees and its role in the management and control of this economically important mite group.